Technique of cavoatrial tumor thrombectomy without cardiopulmonary by-pass - Bhushan Patil; Nikhar Jain; S. K. Patwardhan; Amit Bellurkar (International Brazilian Journal of Urology)
ABSTRACT Introduction Open surgery for tumor thrombi in atria is very challenging and are associated with significant morbidity and mortality rates. Here, we explore safety of foleys catheter assisted-technique, obviating the need for open surgery. Material and Methods We performed Radical nephrectomy via the midlineincision for renal cell carcinoma with tumor thrombus extending into the right atrium. CTVS team was kept in standby all the time. Intra-operative ECHO was used for monitoring any migration of thrombi into pulmonary. Vessels. Results Mean duration of surgery was roughly 4 hours. The time of total IVC occlusion was 2 minutes. The total blood loss was 2350 ml. Intraoperative ECHO showed complete removal of tumor thrombi. Conclusions This procedure can be performed in high risk patients with solitary large tumor thrombi.